Matching Theory for Wireless Networks - Han, Zhu.; Gu, Yunan; Saad, Walid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides the fundamental knowledge of the classical matching theory problems. It builds up the bridge between the matching theory and the 5G wireless communication resource allocation problems. The potentials and challenges of implementing the semi-distributive matching theory framework into the wireless resource allocations are analyzed both theoretically and through implementation examples. Academics, researchers, engineers, and so on, who are interested in efficient distributive wireless resource allocation solutions, will find this book to be an exceptional resource.
1 Introduction -- 2 Fundamentals of Matching Theory -- 3 Stable Marriage Model with Cheating for D2D Communications -- 4 Stable Fixture Model Implementation in LTE V2X Communications -- 5 College Admissions Model for Facebook Content Caching -- 6 Matching with Minimum Quota for Integrated mmWave-Microwave Networks -- 7 Student Project Allocation Model for LTE-Unlicensed -- 8 College Admission Game with Transfers for UL Small Cell Communication -- 9 Conclusion and Future Works.
Keywords: Telecommunication; Computer networks .; Application software; Communications Engineering, Networks; Computer Communication Networks; Computer and Information Systems Applications